Hubungan Antara Dukungan Sosial Teman Sebaya Dengan Quarter Life Crisis Pada Remaja Kelas XII di SMA Negeri 1 Mande Cianjur Tahun 2023 - Riska Setiani; Siti Kamillah; Sancka Stella G. Sihura (Lembaga Pengembangan Kinerja Dosen, 2024)
Quarter life crisis in adolescents during emerging adulthood is someone who is experiencing a period of crisis in the form of anxiety and anxiety about the future and the search for identity. In facing this period of crisis, peer social support is needed which can help early adult individuals to improve their psychological well-being, especially during times of crisis. This research aims to determine the relationship between peer social support and quarter life crisis in class XII teenagers at SMAN 1 Mande Cianjur in 2023. The method used is observational with a cross sectional design. This research involved 77 samples of class XII teenagers at SMAN 1 Mande Cianjur. This research data was obtained through the use of a questionnaire to obtain information about peer social support and quarter life crisis. The results of research on peer social support are low, medium and high peer social support, while for quarter life crisis, namely experiencing a quarter life crisis and not experiencing a quarter life crisis. The results of statistical analysis using the Spearman rank correlation test show that there is a significant relationship between social support from peers and the quarter life crisis (p value = 0.002), which is smaller than 0.05, so Ho is rejected and Ha is accepted. Thus, it can be concluded that there is a relationship between social support from peers and quarter life crisis in class positive self, because the quarter life crisis period is a normal period experienced by every individual.